2004
DOI: 10.1182/blood-2003-04-1069
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B and perforin: constitutive expression in human polymorphonuclear neutrophils

Abstract: Polymorphonuclear neutrophils (PMNs) produce an abundance of bactericidal and cytotoxic molecules consistent with their role as first-line defense against bacterial infection. PMNs, however, also cause efficient cellular cytotoxicity when targeted through Fc receptors to appropriate antibody-coated target cells. Although this so-called antibody-dependent cellular cytotoxicity (ADCC) was described many years ago, the mechanism of killing is still elusive. We now have found that PMNs contain perforin and granzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 35 publications
2
66
3
1
Order By: Relevance
“…It is unclear whether, during killer cell degranulation, the immune synapse forms a perfectly tight gasket that completely prevents granzymes from leaking out into the extracellular space. Moreover, increasing evidence suggests that granzymes may be expressed without perforin and secreted by other types of white blood cells during inflammation, including mast cells, neutrophils, activated macrophages, as well as potentially some nonhematopoietic cells, such as UV-damaged keratinocytes (7,10,11,(176)(177)(178). GzmB is even expressed by developing germ cells in the testes and by syncytial trophoblasts in the placenta (14).…”
Section: Extracellular Roles Of Granzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear whether, during killer cell degranulation, the immune synapse forms a perfectly tight gasket that completely prevents granzymes from leaking out into the extracellular space. Moreover, increasing evidence suggests that granzymes may be expressed without perforin and secreted by other types of white blood cells during inflammation, including mast cells, neutrophils, activated macrophages, as well as potentially some nonhematopoietic cells, such as UV-damaged keratinocytes (7,10,11,(176)(177)(178). GzmB is even expressed by developing germ cells in the testes and by syncytial trophoblasts in the placenta (14).…”
Section: Extracellular Roles Of Granzymesmentioning
confidence: 99%
“…In fact, GzmB has been found in bronchoalveolar lavage fluid after allergen exposure. Several studies have also provided evidence for the expression of GzmB and perforin in human neutrophils, but this is controversial (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] This distribution at first seemed to be wider than that of gzmB, which was thought to be highly restricted to CLs. 25 However, it is now apparent that gzmB is expressed by a great diversity of cell types, including cells of both the myeloid [26][27][28][29] and lymphoid lineages, [30][31][32][33] as well as cells outside the immune system. 22,34,35 Thus, the distribution of SERPINB9 and gzmB predominantly overlaps.…”
Section: Serpinb9 and Granzyme Bmentioning
confidence: 99%
“…Recently, it has been reported that gzmB is present in other leukocyte populations, namely, CD4 þ T cells, 33 B cells, 31 neutrophils, 29 basophils, 28 mast cells, 27 macrophages, 26 dendritic cells 32,52 and CD34 þ stem cells. 29,53 Although the function of gzmB produced by these cells is unknown, it seems to be granule associated.…”
Section: Serpinb9 and Granzyme Bmentioning
confidence: 99%
See 1 more Smart Citation